2015
DOI: 10.12765/cpos-2015-16
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancy by Education, Income and Occupation in Germany: Estimations Using the Longitudinal Survival Method

Abstract: Reliable estimates for differences in life expectancy (LE) by socio-economic position (SEP), that can be assessed in an international context and are comprehensive in terms of considering different SEP dimensions, are missing for the German population so far. The aim of the present study is to fill this gap by providing estimates for differences in LE by education, household income, work status and vocational class. The lack of national mortality data by SEP required an innovative methodological approach to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
(40 reference statements)
1
27
2
2
Order By: Relevance
“…15 Although SES groups were slightly different, education and income/poverty differences (the highest SES group – the lowest SES group) in male and female life expectancy were much smaller in Canada (5 to 8 years) 12 compared with 11 to 16 years noted in our US study. In a German study, 26 differences in life expectancy at age 40 between the highest and lowest educated men and women were 6.3 and 2.3 years respectively, considerably smaller than the corresponding difference of 11 years for men and women in our study. Income differences in life expectancy were also smaller for Germany than for the US.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…15 Although SES groups were slightly different, education and income/poverty differences (the highest SES group – the lowest SES group) in male and female life expectancy were much smaller in Canada (5 to 8 years) 12 compared with 11 to 16 years noted in our US study. In a German study, 26 differences in life expectancy at age 40 between the highest and lowest educated men and women were 6.3 and 2.3 years respectively, considerably smaller than the corresponding difference of 11 years for men and women in our study. Income differences in life expectancy were also smaller for Germany than for the US.…”
Section: Discussioncontrasting
confidence: 92%
“…The findings of our study are consistent with those from previous studies of individual-level socioeconomic differentials in life expectancy. 12 , 15 , 17 , 18 , 26 , 27 Rogot and colleagues found a difference in life expectancy at age 25 of 6 years for white men and 5 years for white women between the highest (master’s degree or higher) and lowest (less than high school) education levels, much smaller than the education differentials shown in our study. 15 Consistent with our study, higher income was associated with higher life expectancy in the Rogot et al study; however, the corresponding income/poverty differential in life expectancy in our study (11 years) was substantially greater than the difference of 5 years reported in their study.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…These age levels are relevant for the overall expenditures of PPV, as the life expectancy of the PPV enrollees is higher than for the average population (zur Nieden and Altis 2017; Gartmann 2004;Luy et al 2015). It is therefore a priory unclear, whether risk exposure works in favor of PPV, as is often claimed (Zimmermann et al 2019; Schulz-Asche 2019; Greß 2019; Rothgang 2018a).…”
Section: How To Deal With Discrepancies In Risk Exposure?mentioning
confidence: 98%
“… Lyu and colleagues (2015) analyzed life expectancy by education, income, and occupation in Germany and found substantial differences between socioeconomic groups. Regarding occupation, their results pointed to a 7-year difference between the lowest and the highest position, and the gap was larger at the age of 40 than at 65 years old and larger among men than women.…”
Section: Introductionmentioning
confidence: 99%